Pre-Settlement and Post-Settlement Stressors and Mental Illness Among Migrants from War-Torn Countries in the Middle East: A Scoping Review - Musa, Mohamad (Journal of Advanced Research in Social Sciences, 2024)
The rising influx of Middle Eastern immigrants from war-torn countries into Canada, the United States, Europe, and Australia underscores the urgent need to understand the stressors they face during pre-settlement and post-settlement phases and their consequent impact on mental health. This scoping review addresses this gap by exploring 16 existing studies on Middle Eastern immigrants’ experiences in these regions published since 1995. The studies were identified through database searches and selected based on specific inclusion and exclusion criteria focused on Middle Eastern immigrants from war-torn countries resettling in North America, Australia, and Europe. The review reveals that immigrants and refugees encounter significant challenges during resettlement, including acculturative stress, loss of status, and existential struggles. These stressors contribute to higher prevalence rates of psychological disorders compared to the general population. Examining the 16 studies predominantly from North America, Australia, and Europe, our review underscores the complex interplay between pre-settlement and post-settlement stressors and mental health outcomes among Middle Eastern immigrants. However, the limited scope of current research highlights the pressing need for further investigation across different continents and regions.